(untitled) (Research, Society and Development, 2021)
Species of Bauhinia L. have been researched for presenting therapeutic properties. The objective was to perform a technological and scientific mapping involving the antimicrobial activities of Bauhinia. A scientific and technological prospection was carried out in international databases of articles and patents, about the antimicrobial activities of Bauhinia. India is the country with the highest number of researches that resulted in publications in the researched databases, with 28, 43 and 48 indexations in Web of Science, Scopus and The Lens, respectively, followed by Brazil and Malaysia. The areas with the highest number of indexed papers were: Pharmacy, Toxicology and Pharmaceutics (31.8%). Patent applications started in 1984 (n=1) reaching a threshold in 2004 (n=18). In the searched databases the United States of America is the largest technology holder among the filing applications (n=153). With respect to CIP 48 patents comprise subclass A61K36. It is concluded that the genus is a source of several researches with antimicrobial actives and it becomes relevant the expansion of technological and scientific productions with species of the taxon.